Penarikan Hibah Dalam KUH Perdata Dengan KHES - Risalan Basri Harahap (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2019)
Grants are allies that are given by people to others for free without any compensation. Granting grants to others can be done by anyone, whether he is a relative or someone who is not a relative. However, these grants are usually given by the closest people who are related by family, whether they are from the lineage or because of association or colleagues. Grants that are given sometimes contain various problems or people who give grants feel sorry for the gifts they do, so in the future there is an intention to withdraw the grants that have already been given. Such a thing has rules that explain it both in the Civil Code and in the KUHE. Based on the results of the analysis of the writer that in the Civil Code about the provisions of the amount of grant assets there is no maximum limit set, only emphasizes that not to reduce the absolute part (legitiemeportie) for the legitimate. Meanwhile, according to the Sharia Economic Law Compilation, the limit on the amount of grant assets is only 1/3 of the donor's assets, if it exceeds the provisions, the grant recipient must return the excess. Withdrawal of assets that have been donated in the Civil Code is not permitted except for three reasons, namely: first, because the conditions for granting are not fulfilled, second, because the recipient of a mistake has made a mistake with the intention of committing or helping to commit a crime, third, because the recipient of the grant refuses provide subsistence allowance after falling into poverty. While the withdrawal of assets that have been granted in KHES is permitted, namely parent grants to children, but the withdrawal of grants to others is not permitted.